Endoscopic resection of upper gastrointestinal lymphangioma: A single-center experience - Shi, Ziyu; Huang, Xue; Li, Keliang; Tu, Qiuyue; Liu, Dan; Zhao, Lixia; Yang, Huiyu; Li, Deliang; Zhao, Yue; Zhang, Jiyu; Li, Muhan; Liu, Bingrong (Frontiers in Oncology, 2022)
Objective Lymphagioma, which in most cases as benign tumors, occurs in head, neck, axilla, and mediastinum. Lymphangioma is exceedingly rare in the upper gastrointestinal tract including esophagus, stomach, and duodenum. However, the clinical characteristics, natural history, and recurrence rate after endoscopic resection remain unclear. This study aims to evaluate the characteristic findings and assess the efficacy of endoscopic techniques in the management of this disease. Methods In this systematic retrospective analysis, we evaluated all 24 cases of upper gastrointestinal lymphangioma resected by endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD) and diagnosed by histopathology at our hospital from January 2012 to May 2021. We analyzed the results of endoscopy, endoscopic ultrasonography (EUS), CT, histologic examination, and follow-up assessments. Results 9 male and 15 female patients with esophageal lymphangioma were enrolled in this study, with a mean age of 54.17±11.60 years (range 30-71 years). The lesions’ size varied from 2.20 to 40.10 mm, with the median size of 7.83 mm. All patients were evaluated preoperatively, whose endoscopic appearance typically appears as dilated lymphatic channels beneath the surface epithelium of the protrude mucosal or sub-mucosal lesion. Endoscopic ultrasonography revealed the presence of a honeycomb-like or grid-like mass with a heterogeneous echo pattern, and a clear boundary between the lesion and the muscularis propria layer may be helpful for the primary diagnosis of this disease. 22 patients underwent EMR and 2 patient was treated with ESD. Histologic examination revealed that the lesions contained many dilated lymphatic vessels, which confirmed the initial diagnosis of lymphangioma in all patients. No major adverse events were found during the operation or a median follow-up of 43 months (range 13–92). Conclusions Endoscopic ultrasonography has important clinical value for the primary diagnosis of lymphangioma in the upper gastrointestinal tract. This study also suggests that endoscopic resection should be considered as a more minimally invasive, safe, feasible, and effective therapeutic option comparing to laparoscopic surgery.